"I've just never done that:" The influence of transitional anxiety on post‐incarceration reentry and reintegration experiences among veterans. (11th July 2021) - Hyde, Justeen; Bolton, Rendelle; Kim, Bo; Yakovchenko, Vera; Petrakis, Beth A.; Visher, Christy; McInnes, Keith
Abstract: Military veterans involved in the criminal justice system are a vulnerable subpopulation that has extensive physical and behavioural health treatment needs. Like non‐veteran populations, safe and stable housing, employment and social support are critical for veterans returning to society after incarceration. The challenges of social reintegration are immense, and the risk of recidivism is high. The U.S. Department of Veteran Affairs (VA) has developed specific programmes to assist veterans plan for and assist with reentry. While there have been successes, recidivism and early mortality are persistent concerns. This study examined reentry experiences of veterans living in one northeastern state to gain a better understanding of factors that influence social reintegration. The study was conducted in 2017 to inform an enhancement of VA reentry services through the addition of peer support. Qualitative interviews were conducted with 16 veterans with recent incarceration experiences and 27 reentry specialists working in five correctional facilities, two VA hospitals, five community agencies and two state departments. Interview transcripts were reviewed and coded using a Framework Analysis approach. Narratives highlight high levels of anxiety and uncertainty experienced as participants went through physical and emotional transitions associated with reentry and reintegration. This 'transitional anxiety' was often rooted in the absence of prior positive experiences engaging in socially normative activities, like obtaining housing and employment. Embarrassment and shame regarding a lack of experience with expected responsibilities were commonly reported. Although salient in veterans' narratives, reentry specialists rarely talked about problems post‐incarceration in terms of limited life experience and skills, focusing instead on substance use and mental health issues. Few resources were available to support the development of critical life skills. Findings call attention to the need for understanding pre‐incarceration experiences that may influence social reintegration and the development of tailored interventions to build skills and experience when needed.